Social participation in inclusive physical education: On the importance of class, teaching methods and teacher characteristics - Vitus Furrer (Bern Open Publishing, 2023)
Inclusive education aims to give all children access to the general education system, regardless of their disposition, and thereby reduce social exclusion. The aim is to achieve equal participation in society called for in the Convention on the Rights of Persons with Disabilities. In many countries, including Switzerland, this has led to the increased integration of children with special educational needs into mainstream schools in recent years. However, studies show that the social participation of children with special educational needs in inclusive classes is often accompanied by challenges. Compared to their peers, children with special educational needs have fewer interactions and friendships and are less accepted. In particular, children with intellectual disabilities are at risk of social exclusion. Regarding reduced social participation, inclusive physical education is seen as having a particular potential to promote this participation. However, joint teaching alone is no guarantee that children with and without special educational needs are equally involved in social processes in their class. In inclusive physical education, social exclusion can be particularly visible and tangible, as the learners' physicality is more in focus than in other subjects. In inclusion research, it is therefore of interest how social participation can be promoted. In the field of inclusive physical education with children with intellectual disabilities, however, there is hardly any empirical knowledge on this. This dissertation addresses this research gap and investigates how aspects of social participation of children with intellectual disabilities are shaped in inclusive physical education and which factors are related to them. The data for the three manuscripts submitted for the dissertation all come from the SoPariS research project, which focuses on inclusive physical education with children with intellectual disabilities. In 2019, a cross-sectional study with quantitative questionnaires was conducted for pupils and physical education teachers, surveying 109 primary school classes (3rd-6th grade). Multilevel regressions and social network analysis show that children with intellectual disabilities receive significantly less social interaction (Furrer et al., 2021, 2020) and are less accepted (Furrer et al., in press) than their peers without disability. At the same time, there are fewer social interactions in physical education than in classroom teaching (Furrer et al., in press). The individual reference norm orientation of the physical education teacher is positively related to social acceptance and social interactions, whereby these are particularly increased for children with intellectual disabilities. Furthermore, teaching cooperative norms is positively related to children's social acceptance (Furrer et al., 2020). However, social interactions are not related to the physical education teacher's attitude towards inclusive teaching (Furrer et al., 2021). Finally, social interactions in both physical education and classroom teaching are positively related to classroom climate (Furrer et al., in press). In summary, it can be stated that the investigated aspects of social participation of children with intellectual disabilities are significantly lower than those of children without intellectual disabilities, even in inclusive physical education at primary school level. Specifically, social interactions and acceptance are below average. However, factors could be identified that are positively related to social participation. The great challenge of integrating children with special educational needs is to make teachers aware of the importance of social processes in the classroom and to train and develop them in this area. While the manuscripts of this dissertation provide valuable insights into the promotion of social participation of children with special educational needs in inclusive classrooms, further longitudinal intervention studies are needed to investigate the direction of impact of these factors and to show change over time. References Furrer, V., Mumenthaler, F., Eckhart, M., Nagel, S., & Valkanover, S. (in press). Zum Zusammenhang von Klassenklima und sozialen Interaktionen. Ein Vergleich zwischen inklusivem Klassenzimmer- und Sportunterricht [On the relationship between classroom climate and social interactions. A comparison between inclusive classroom and physical education teaching]. Zeitschrift für sportpädagogische Forschung. Furrer, V., Mumenthaler, F., Valkanover, S., Eckhart, M., & Nagel, S. (2021). Zum Zusammenhang zwischen der Einstellung der Lehrkraft zu inklusivem Sportunterricht und sozialer Interaktionen von Kindern [On the relationship between teacher attitudes towards inclusive physical education and children's social interactions]. Zeitschrift für Grundschulforschung, 14, 237-256. https://doi.org/10.1007/s42278-021-00108-9 Furrer V., Valkanover S., Eckhart M., & Nagel S. (2020). The role of teaching strategies in social acceptance and interactions; Considering students with intellectual disabilities in inclusive physical education. Frontiers in Education, 5, Article 586960. https://doi.org/10.3389/feduc.2020.586960